Mitigating the Effects of Habitat Loss on Solitary Bees in Agricultural Ecosystems - Olivia Kline; Neelendra K. Joshi (Agriculture, 2020)
Solitary bees and other wild pollinators provide an important ecosystem service which can benefit both the agricultural economy and the sustainability of many native ecosystems. Many solitary bees, however, are experiencing decreases in their populations and ranges, resulting in an overall loss of pollinator species richness in many areas. Several interacting factors have been implicated in this decline, including increased pesticide use, climate change, and pathogens, but habitat loss remains one of the primary drivers. The widespread conversion of natural habitats into agricultural landscapes has decreased the availability of adequate nesting sites and floral diversity for many bee species. Large monocultures with intensive production systems often cannot support the populations of wild bees (particularly species with short foraging ranges) necessary to ensure adequate pollination of animal-pollinated crops. Diversifying agricultural landscapes through the incorporation of wildflower plantings, as well as the preservation of remaining natural habitats, may offer a solution, as it has been shown to increase both bee diversity and abundance and the pollination of nearby crops. In this review article, we discuss the various effects of habitat loss on solitary bees and different ways to mitigate such effects in order to conserve bee diversity and populations in agricultural landscapes.